2009
DOI: 10.1182/blood-2008-05-155952
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, a cancer chemopreventive and chemotherapeutic agent, is a biologically active iron chelator

Abstract: Curcumin is a natural product currently in human clinical trials for a variety of neoplastic, preneoplastic, and inflammatory conditions. We previously observed that, in cultured cells, curcumin exhibits properties of an iron chelator. To test whether the chelator activity of curcumin is sufficient to induce iron deficiency in vivo, mice were placed on diets containing graded concentrations of both iron and curcumin for 26 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
178
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(191 citation statements)
references
References 52 publications
8
178
4
1
Order By: Relevance
“…Curcumin was recently found to be an active iron chelator in vivo and to induce a state of overt iron deficiency anemia in mice fed with diets poor in iron. 58 This suggests that curcumin has the potential to affect systemic iron metabolism, particularly in people with suboptimal iron status. 58,59 Curcumin has also been shown to inhibit the activity of the drug-metabolizing enzymes cytochrome P450, glutathione-S-transferase, and UDP-glucuronosyltransferase.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin was recently found to be an active iron chelator in vivo and to induce a state of overt iron deficiency anemia in mice fed with diets poor in iron. 58 This suggests that curcumin has the potential to affect systemic iron metabolism, particularly in people with suboptimal iron status. 58,59 Curcumin has also been shown to inhibit the activity of the drug-metabolizing enzymes cytochrome P450, glutathione-S-transferase, and UDP-glucuronosyltransferase.…”
Section: Dear Editormentioning
confidence: 99%
“…58 This suggests that curcumin has the potential to affect systemic iron metabolism, particularly in people with suboptimal iron status. 58,59 Curcumin has also been shown to inhibit the activity of the drug-metabolizing enzymes cytochrome P450, glutathione-S-transferase, and UDP-glucuronosyltransferase. 8,[60][61][62] The inhibition of these enzymes in people taking curcumin may lead to an undesired increase in the plasma concentrations of some drugs and cause toxicity.…”
Section: Dear Editormentioning
confidence: 99%
“…Curcumin has been shown to act as a cancer chemopreventive and chemotherapeutic agent (Chuang, 2000;Goel et al, 2008;Hatcher et al, 2008;Jiao et al, 2008). Curcumin, a polyphenolic compound, has been successfully used for treatment of various diseases such as allergies, arthritis, diabetes, Alzheimer's disease and other chronic diseases Manolova et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the encouraging preclinical and phase I clinical data, several additional human trials have been initiated and are currently enrolling patients. This includes trials testing the activity of curcumin in patients with colon cancer, pancreatic cancer, multiple myeloma, and myelodisplasia (Jiao et al, 2009). Nanoparticles have promising applications in medicine (Jiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It can suppress TNF expression induced by numerous stimuli and in numerous cell types. Recent work has suggested that curcumin acts as a cancer chemopreventive and chemotherapeutic agent (Chuang et al, 2000;Goel et al, 2008;Hatcher et al, 2008;Jiao et al, 2009). Curcumin inhibits activation of nuclear factor κB through blockade of IκB kinase, and inhibits activation of cyclooxygenase 2 (COX2).…”
Section: Introductionmentioning
confidence: 99%